Internal Auditing Practices And Performance Of Internal Audit Department - HJ. FADZIL, FAUDZIAH HANIM (2003)
The performance of an internal audit department must function in a manner that is in accordance with applicable professional standards such as Standards for the Professional Practice of Internal Auditing (SPPIA, 2000) and the quality of the internal control systems.